MODEL PENYELESAIAN SENGKETA PERTANAHAN MELALUI MEDIASI DALAM MEWUJUDKAN PENYELESAIAN YANG EFISIENSI DAN BERKEPASTIAN HUKUM - Sri Hajati; Agus Sekarmadji; Sri Winarsih (Jurnal Dinamika Hukum, 2014)
Dispute settlement of land cases through the court contains many drawbacks such as bureaucratic barrier and time-consuming effort and cost. Although the principles of dispute resolution in the court claim that it takes short time and low costs, it remains difficult to implement. One of alter-native ways on dispute resolution land cases can be conducted through suitable mediation. Thus, the management, assessment and case management of land performed the National Land Agency along with the whole component of society in guaranteeing land cases can be quickly resolved. Key words: dispute settlement, mediation, legal certainty.